NOMINAL AFFIXATION BETWEEN ENGLISH AND BATAK TOBA LANGUAGE - Elisa B. Manullang (BAHAS, 2016)
This study deals with Nominal Affixation in English and Batak Toba language. This article focuses on Nominal Afixation in Batak Toba Language and English particularly derivational noun from Adjectives stems. The data were obtained by conducted descriptive Qualitative design. The data were analyzed into their stems and affixes and formulated the system of the language. Based on the steps was found out ha + adjectives stems + on in Batak Toba language Nominal Affixation was responded to adjectives stems -ness, -ity, -ce, -th, -cy in English. It shows that one item in Batak Toba language become two or more in English. Keyword : Nominal Affixation, Batak Toba Language, derivational noun, Adjective stem.